Electrochemical sensor, graphite foil electrode for monitoring carbendazim and preparation method thereof

Graphite foil electrode prepared by multipotential step technology solves the problems of complex preparation of existing graphene electrodes and poor electrocatalytic performance, and achieves high sensitivity and low detection limit multi-bacterial detection, with good reusability .

CN118746608BActive Publication Date: 2025-02-14ZHAOQING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410750690.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-02-14
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing graphene electrode preparation process is complicated, the electrocatalytic performance is poor, and the detection efficiency and detection accuracy cannot be taken into account in the detection of wormwood.

Method used

Multipotential step technology is used to apply step potential to graphite foil, control the peeling degree, defect degree and nitrogen-oxygen doping degree, and prepare graphite foil electrodes with specific nitrogen-oxygen doping ratio and partially peeled off. The electrode surface forms graphene nanosheets that are uprightly distributed and seamlessly connected to the graphite foil substrate, increasing the electrode active surface area and ensuring continuous conductive pathways.

Benefits of technology

The electron transfer capability and electrocatalytic performance of graphite foil electrodes are significantly improved, and the electron transfer capability and electrocatalytic performance of the graphite foil electrodes are excellent and the detection limit is low. The detection method is simple and the electrode reusability is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118746608B_ABST
    Figure CN118746608B_ABST
Patent Text Reader

Abstract

The present invention relates to an electrochemical sensor, a graphite foil electrode for monitoring carbendazim and a preparation method thereof, wherein the graphite foil electrode for monitoring carbendazim comprises: a graphite foil substrate and graphene nanosheets vertically and uprightly distributed on the surface of the graphite foil substrate, wherein the graphene nanosheets and the graphite foil substrate are seamlessly connected; the graphene nanosheets and the graphite foil substrate are prepared by electrochemical stripping of a piece of graphite foil; the oxygen content in the graphite foil electrode is 15%-25%; and the nitrogen content is 3%-10%. The beneficial effect is that the graphite foil electrode, as a self-supporting electrode, can be directly used as a working electrode of an electrochemical sensor. The cost of the raw material graphite foil is low, the preparation method of the graphite foil electrode is simple, the electrode has high reusability, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical materials, and in particular to an electrochemical sensor, a graphite foil electrode for monitoring carbendazim and a preparation method thereof. Background Art

[0002] Electrochemical sensors are increasingly used in the field of analytical detection due to their advantages such as fast detection speed, high sensitivity, and convenient instrumentation. Electrode materials are the key factors that determine the performance of electrochemical sensors. Traditional electrochemical sensor electrodes are constructed by directly using solid electrodes such as glassy carbon electrodes (GCE), Pt electrodes, and Au electrodes as working electrodes or as conductive carriers, and modifying electrochemically active nanomaterials such as graphene, transition metal oxides, and conductive polymers on their surfaces. However, the above-mentioned modified electrodes are expensive, the electrode preparation process is complicated, and the reproducibility of electrode performance is affected. On the other hand, the powdered graphene sheets in the modified electrodes are prone to restacking, resulting in a reduction in their electrochemically active area. In addition, the use of non-electrochemically active adhesives and the difficulty in forming a smooth conductive network between graphene sheets and solid electrode heterogeneous carriers have hindered the effective use of graphene's excellent conductive properties.

[0003] Electrochemical exfoliation is an effective method for preparing high-quality graphene. In the prior art, the exfoliated graphene sheets or graphite layers are separated from the graphite matrix more thoroughly, and the graphene will completely fall off the graphite substrate, so what is prepared is a highly dispersed graphene aqueous solution. Therefore, in order to obtain a graphene-based electrode, subsequent production is required. However, in the subsequent production process of the graphene electrode, the graphene sheets will spontaneously stack, resulting in a decrease in the effective electrochemical active area of ​​the electrode, and accompanied by an increase in internal resistance, the electrocatalytic performance is poor.

[0004] Carbendazim (CBZ) is a kind of fungicide widely used in the process of plant cultivation. It is used to prevent and control diseases caused by fungi because it mainly interferes with the genetic metabolism process in organisms. Compared with other pesticides, CBZ itself has lower toxicity, but its chemical properties are stable and difficult to degrade in the natural environment, resulting in a large amount of accumulation of CBZ, which seriously pollutes the living environment of animals and plants. As people pay more and more attention to food safety and ecological environmental pollution, rapid detection of CBZ content in water, crops, etc. is of great significance. At present, the common methods for detecting CBZ mainly include chromatography, spectrophotometry and immunoassay. Although these detection methods can detect the content of carbendazim, they each have their own shortcomings. Chromatography has high accuracy, but the sample pretreatment is complicated and the operation is cumbersome; spectrophotometry has many consumables and poor accuracy; immunoassay antibody preparation is complicated.

[0005] Therefore, it is necessary to develop new electrochemical sensor electrodes to solve the above problems existing in the current CBZ detection. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides an electrochemical sensor, a graphite foil electrode for monitoring carbendazim and a preparation method, which solves the technical problems that the current graphene electrode preparation process is complicated, the electrocatalytic performance is poor, and the detection efficiency and detection accuracy cannot be taken into account in CBZ detection.

[0008] (II) Technical solution

[0009] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0010] In the first aspect, an embodiment of the present invention provides a graphite foil electrode for monitoring carbendazim, comprising: a graphite foil substrate and graphene nanosheets vertically distributed on the surface of the graphite foil substrate, wherein the graphene nanosheets and the graphite foil substrate are seamlessly connected; the graphene nanosheets and the graphite foil substrate are obtained by electrochemically exfoliating a piece of graphite foil; the graphite foil electrode has an oxygen content of 15%-25%; and a nitrogen content of 3%-10%.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing a graphite foil electrode, comprising the following steps: S1, preparing a nitrate solution with a concentration of 0.5-2M for use as an intercalation reagent; S2, using the intercalation reagent as an electrolyte, and using the graphite foil as a working electrode, and forming a three-electrode system with an auxiliary electrode and a reference electrode; S3, using a multi-potential step technology to apply a step potential to the working electrode, and with the participation of nitrate ions, obtaining a nitrogen-oxygen doped partially exfoliated graphite foil electrode; wherein the step potential is two cathode potential cycles, or one anode potential and one cathode potential cycle.

[0012] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S3, the step potential is two cathode potential cycles: the first cathode potential is -0.2V to -0.6V, maintained for 18-25s; the second cathode potential is -1.7V to -2.1V, maintained for 8-15s; and the cycle is 2-12 times.

[0013] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S3, when the two cathode potentials are cycled: the first cathode potential is -0.6V, maintained for 20s; the second cathode potential is -2.1V, maintained for 10s; and the cycle is repeated twice.

[0014] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S3, the step potential is an anode potential and a cathode potential cycle: the anode potential is 0.2V to 1.2V, maintained for 18-25s; the cathode potential is -1.5V to -2.6V, maintained for 8-15s; cycled 2-14 times; the absolute value range of the difference between the anode potential and the cathode potential is 2.7-3.1V.

[0015] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S3, the step potential is an anode potential and a cathode potential cycle: the anode potential is 0.6V, maintained for 20s; the cathode potential is -2.1V, maintained for 10s; and the cycle is repeated 10 times.

[0016] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S1, the concentration of the nitrate solution is 1.5M; the nitrate is selected from one of sodium nitrate, potassium nitrate and ammonium nitrate.

[0017] As a preferred embodiment of the present invention, in the method for preparing the graphite foil electrode, in S2, the working area of ​​the graphite foil is 0.09-4 cm 2 .

[0018] In a third aspect, an embodiment of the present invention provides an electrochemical sensor, which comprises the graphite foil electrode described in the first aspect or a graphite foil electrode prepared by the preparation method described in any one of the preparation methods in the second aspect.

[0019] As a preferred embodiment of the present invention, the electrochemical sensor is a carbendazim detection sensor.

[0020] (III) Beneficial effects

[0021] The beneficial effects of the present invention are as follows: the electrochemical sensor, the graphite foil electrode for monitoring carbendazim and the preparation method of the present invention are beneficial to control the degree of stripping, the degree of defects and the degree of nitrogen and oxygen doping due to the multi-potential step technology applied to the graphite foil. With the participation of nitrate ions, the step potential is two cathode potential cycles, or one anode potential and one cathode potential cycle, and a graphite foil electrode with a specific nitrogen and oxygen doping ratio and partial stripping is prepared. The upright distribution and graphene nanosheets seamlessly connected to the graphite foil substrate formed by the peeling of the graphite foil surface increase the active surface area of ​​the electrode, and ensure a continuous conductive path, which can greatly improve the electron transfer capacity. At the same time, the graphite foil electrode introduces oxygen-containing groups and nitrogen atoms, which can produce a unique catalytic effect and activity on the electrochemical behavior of specific substances, which is beneficial to the application of electrochemical detection. Compared with the prior art, the graphite foil electrode shows excellent electrocatalytic performance for carbendazim detection, and can effectively reduce the background current, thereby constructing a carbendazim electrochemical detection method with high sensitivity, low detection limit and simple detection method. Among them, the detection limit of carbendazim is as low as 0.24nM. As a self-supporting electrode, the graphite foil electrode can be directly used as the working electrode of the electrochemical sensor. The raw material graphite foil has low cost, the preparation method of graphite foil electrode is simple, the electrode is highly reusable, and has good application prospects.

[0022] When the electrolyte is a 0.5-2M nitrate solution and the nitrate solution is used as an intercalation agent, in the two cathode potential cycles, the first cathode potential is -0.2V to -0.6V, maintained for 18-25s; the second cathode potential is -1.7V to -2.1V, maintained for 8-15s; the two cathode potentials are cycled 2-12 times. It can ensure the degree of graphite foil stripping, defect degree and nitrogen-oxygen doping ratio. The prepared electrode meets the requirements of high peak current and its signal-to-noise ratio during CBZ detection, small background current, and is conducive to trace detection. Among them, the electrolyte is 1.5M, the first cathode potential is -0.6V, maintained for 20s, the second cathode potential is -2.1V, maintained for 10s, and the two cathode potentials are cycled twice, which is the best state for cathode potential stripping treatment.

[0023] When the electrolyte is a 0.5-2M nitrate solution and the nitrate solution is used as an intercalation agent, an anode potential and a cathode potential cycle: the anode potential is 0.2V to 1.2V, maintained for 18-25s; the cathode potential is -1.5V to -2.6V, maintained for 8-15s; an anode potential and a cathode potential cycle 2-14 times; the difference between the anode potential and the cathode potential ranges from 2.7 to 3.1V. It can ensure the degree of graphite foil stripping, defect degree and nitrogen and oxygen doping ratio. The prepared electrode meets the requirements of high peak current and its signal-to-noise ratio during CBZ detection, small background current, and is conducive to trace detection. Among them, the electrolyte is 1.5M, the anode potential is 0.6V, maintained for 20s, the cathode potential is -2.1V, maintained for 10s, and an anode potential and a cathode potential are cycled 10 times, which is the best state for alternating stripping treatment of anode potential and cathode potential.

[0024] As can be seen from the above, the cathode-cathode potential step cycle or the anode-cathode potential step cycle is adopted in the present invention, wherein a relatively strong cathode potential (i.e., a cathode potential with a relatively large absolute value) is set. Under the strong reducing property of the strong cathode potential, a small amount of cation intercalation and hydrogen generated by water electrolysis expand and peel off the graphite sheets, and the number of peeled layers is large, providing a larger specific surface area for the graphite foil electrode. At the same time, the graphite foil electrode has fewer oxygen-containing groups and carbon lattice defects, and has a strong conductivity.

[0025] A weak cathode potential or a weak anode potential is used in combination with a strong cathode potential to provide weak oxidizing properties. On the one hand, it can prevent the strong cathode from reducing the original oxygen elements in the graphite foil and affecting the hydrophilicity of the electrode. On the other hand, nitrogen and oxygen doping can be achieved to ensure the binding ability with the analyte, thereby exerting a high-efficiency electrocatalytic effect on the analyte; at the same time, because the diameters of carbon atoms and nitrogen atoms are close, nitrogen doping has little destructive effect on the carbon lattice, and can also increase the conductivity of the graphite foil electrode, with a small background current. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 are SEM images, where A and B correspond to EG-A electrodes, C and D correspond to EG-C electrodes, and E and F correspond to EG-AC;

[0027] Figure 2 XPS spectra of G electrode, EG-A electrode, EG-C electrode and EG-AC electrode;

[0028] Figure 3 C1s XPS spectra of G electrode, EG-A electrode, EG-C electrode and EG-AC electrode;

[0029] Figure 4 Raman spectra of G electrode, EG-A electrode, EG-C electrode and EG-AC electrode;

[0030] Figure 5 , where A is the Raman spectra of the G electrode and the EG-A electrode, the EG-C electrode and the EG-AC electrode, and B is the Nyquist plot of the G electrode and the EG-A electrode, the EG-C electrode and the EG-AC electrode;

[0031] Figure 6 , where A is the CV curves of G electrode and EG-A electrode, EG-C electrode and EG-AC electrode in PBS containing 50 μM CBZ; B is the DPV curves of G electrode and EG-A electrode, EG-C electrode and EG-AC electrode in PBS containing 50 μM CBZ; C is the DPV curves of G electrode and EG-A electrode, EG-C electrode and EG-AC electrode in PBS containing 1 μM CBZ;

[0032] Figure 7 , where A is the DPV curve of EG-AC electrode in PBS solutions of different pH values ​​containing 1 μM CBZ; B is the curve of the relationship between the peak potential of CBZ and pH;

[0033] Figure 8 , where A is the DPV curve overlay of EG-AC electrode in 0.001-3μM CBZ; B is the CBZ standard curve;

[0034] Fig. 9 It is a bar graph showing the effects of different interferents on the peak current value of CBZ. DETAILED DESCRIPTION

[0035] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0036] The electrochemical sensor, graphite foil electrode for monitoring carbendazim and preparation method proposed in the embodiment of the present invention are aimed at the technical problems that the current graphene electrode preparation process is complicated, the electrocatalytic performance is poor, and the detection efficiency and detection accuracy cannot be taken into account in CBZ detection. The multi-potential step technology is used to apply a step potential to the graphite foil, which is conducive to controlling the degree of stripping, the degree of defects and the degree of nitrogen and oxygen doping. With the participation of nitrate ions, the step potential is two cathode potential cycles, or one anode potential and one cathode potential cycle, and a graphite foil electrode with a specific nitrogen and oxygen doping ratio and partial stripping is prepared. The upright distribution and graphene nanosheets seamlessly connected to the graphite foil substrate formed by the peeling of the graphite foil surface increase the active surface area of ​​the electrode, and ensure a continuous conductive path, which can greatly improve the electron transfer capacity. At the same time, the graphite foil electrode introduces oxygen-containing groups and nitrogen atoms, which can produce a unique catalytic effect and activity on the electrochemical behavior of specific substances, which is conducive to electrochemical detection applications. Compared with the existing technology, the graphite foil electrode shows excellent electrocatalytic performance for the detection of carbendazim and can effectively reduce the background current, thus constructing an electrochemical detection method for carbendazim with high sensitivity, low detection limit and simple detection method. Among them, the detection limit of carbendazim is as low as 0.24nM. As a self-supporting electrode, the graphite foil electrode can be directly used as the working electrode of the electrochemical sensor. The raw material graphite foil has low cost, the preparation method of the graphite foil electrode is simple, the electrode has high reusability, and has good application prospects.

[0037] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0038] Example 1

[0039] This embodiment provides a method for preparing a graphite foil electrode, comprising the following steps:

[0040] (1) Prepare a 1.5 M potassium nitrate solution as an intercalation reagent; use a commercial graphite foil with a thickness of 0.3 mm and cut it into 0.3 × 0.8 cm 2 Size, sealed with insulating tape, fixed working area is 0.3×0.3cm 2 ,spare;

[0041] (2) A three-electrode system was formed with cut graphite foil, Pt sheet and saturated calomel electrode as working electrode, auxiliary electrode and reference electrode respectively. In 1.5 M potassium nitrate solution, two potentials were applied to the working electrode using the multi-potential step (STEP) technique, and the two potentials were alternately switched to electrochemically exfoliate and functionalize the graphite foil;

[0042] Among them, a cathode potential and an anode potential were used for stepping, and potential 1 was set to an anode potential of 0.6 V for 20 s; potential 2 was set to a cathode potential of -2.1 V for 10 s. The cycle was repeated 10 times, and the prepared electrode was named EG-AC electrode.

[0043] Embodiment As the best embodiment, under the above electrochemical stripping conditions, the peak current detected by CBZ reaches the maximum.

[0044] Example 2

[0045] This embodiment provides a method for preparing a graphite foil electrode. The difference from Embodiment 1 is that in step (2), two cathode potentials are used for stepping, and potential 1 is set to -0.6 V for 20 s; potential 2 is set to -2.1 V for 10 s, and the cycle is repeated twice. The prepared electrode is named EG-C electrode.

[0046] Comparative Example 1

[0047] This comparative example provides a method for preparing a graphite foil electrode, which is different from Example 1 in that in step (2), two anode potentials are used for stepping, and potential 1 is set to 0.6 V and the time is 20 s; potential 2 is set to 2.1 V and the time is 10 s, and the cycle is repeated twice. The prepared electrode is named EG-A electrode.

[0048] The graphite foil electrodes prepared in Example 1, Example 2 and Comparative Example 1 were characterized by SEM technology for microscopic morphology. Figure 1 As shown in the figure, after electrochemical treatment in different potential ranges, the surface of the graphite foil electrode is peeled off to varying degrees, forming a large number of upright graphene nanosheets, which greatly increases the specific surface area of ​​the electrode and provides a large number of active sites for subsequent detection of the analyte. Figure 1 As shown in A and B, the graphene sheets formed by the EG-A electrode stripped by the anode in Comparative Example 1 are more and thinner, because the anode treatment mainly passes through NO 3- The insertion of anions into the graphene interlayers and the oxidation reaction on the electrode cause CO2, O2, and NO2 to be produced in the graphene gaps for exfoliation, so the exfoliation efficiency is high and graphene nanosheets with fewer layers can be obtained.

[0049] like Figure 1As shown in C and D, upright graphene can be observed on the surface of the cathode-stripped EG-C electrode in Example 2. Compared with the EG-A electrode, thicker graphene nanosheets are formed, and larger pore structures are formed between the nanosheets. This is because the cathode mainly relies on cation intercalation and the electrolysis of water to produce hydrogen to expand the graphite sheets, and the number of inserted cations is relatively small.

[0050] like Figure 1 As shown in Figures E and F, the surface morphology of the EG-AC electrode after alternate peeling of the cathode and cathode in Example 1 is similar to that of the EG-C electrode, and a macroporous structure is also formed between the graphene nanosheet layers. The above-mentioned upright graphene nanosheets are seamlessly connected to the carbon paper substrate, and a continuous conductive path is formed, which can greatly improve the electron transfer capacity, and the three-dimensional macroporous network structure is conducive to the mass transfer process, providing a path for the analyte to quickly diffuse to the electrode surface.

[0051] Using XPS technology, the chemical composition of EG-A electrode, EG-C electrode and EG-AC electrode was analyzed with the graphite foil electrode (G electrode) without electrochemical treatment as reference. Figure 2 , the G electrode is composed of only C (94.28%) and O (5.72%) elements. After electrochemical treatment in different potential ranges, in addition to C elements, N and O elements were introduced on the surfaces of the EG-A electrode, EG-C electrode and EG-AC electrode. Among them, the O atom content was 39.3%, 18.77% and 23%, respectively; the N atom content was 21.36%, 4.47% and 8.12%, respectively, indicating that after electrochemical stripping and functionalization treatment, a large number of N and O functional groups were doped on the surface of the graphite foil. The content of functional groups is closely related to the electrochemical treatment potential. The nitrogen and oxygen group content of the anodic stripped EG-A is much higher than that of the cathodic stripped EG-C, while the nitrogen and oxygen group content of EG-AC is between the two, slightly higher than EG-C. The oxygen-containing groups may come from the oxidation of the carbon electrode; the N-containing groups may come from the electrode's reaction to NO 3- In addition, N atoms may be embedded into the carbon lattice during the electrochemical treatment.

[0052] refer to Figure 3 , the C1s XPS spectra of four samples of G electrode, EG-A electrode, EG-C electrode and EG-AC electrode were analyzed. Among them, Figure 3 Figure A in the middle is the C1s XPS spectrum of the G electrode, which can be decomposed into two fitting peaks, corresponding to the electron binding energy signals of the C=C / CC bond (284.6 eV) and the CO bond (285.7 eV). Figure 3 Figure B is the C1s XPS spectrum of the EG-A electrode, which can be decomposed into five fitting peaks, corresponding to sp 2Binding energy signals of C (284.3 eV), C-OH / C=N (285 eV), COC (286.6 eV), CN / C=O (287.2 eV) and OC=O (288.7 eV). Figure 3 Figure C corresponds to the EG-C electrode, and Figure D corresponds to the EG-AC electrode. It can be seen that the C1s XPS spectra of the EG-C electrode and the EG-AC electrode can be decomposed into three peak fitting peaks, corresponding to sp 2 The binding energy signals of C (283.8eV), C=N (284.6eV) and COC (285.8eV). The above results show that the N and O functional groups on the surface of the EG-A electrode, EG-C electrode and EG-AC electrode after different electrochemical treatments are connected to the carbon skeleton through chemical bonds. Especially for EG-A prepared by pure anodic potential, a large number of N and O atoms are doped into the carbon skeleton, and excessive heteroatom doping, especially oxygen atom doping, destroys the graphite lattice, resulting in a significant decrease in the conductivity of the electrode. The EG-C electrode prepared by cathode-cathode potential step cycle and the EG-AC electrode prepared by anode-cathode potential step cycle have a low degree of oxidation, which keeps the carbon electrode in good conductivity. At the same time, the appropriate amount of nitrogen oxide groups can improve the wettability of the electrode and enhance the interaction with the analyte.

[0053] Raman spectroscopy was used to characterize the G electrode, EG-A electrode, EG-C electrode and EG-AC electrode. Figure 4 , among which 4 samples all showed D peak, G peak and 2D peak of carbonaceous materials. -1 ) is related to the in-plane stretching vibration mode (E2g) of the hexagonal carbon lattice. The D peak (-1350cm -1 ) is related to the degree of defects in the graphite structure. D / I G The strength of the graphite is proportional to the defect level of the graphite structure. D / I G =0.14) compared to EG-A(I D / I G =1.04), EG-AC(I D / I G =0.73) and EG-C(I D / I G =0.64) electrode has a higher I D / I G The value of I of EG-A indicates that the surface disorder of the peeled EG electrode is high. D / I GThe value is the highest, indicating that its defect degree is high, which is related to the introduction of a large number of oxygen-containing groups during the anodic stripping process. EG-C obtains graphene sheets with lower defect and oxidation degree. Compared with EG-C, the defect and oxidation degree of EG-AC are slightly higher.

[0054] Electrochemical characterization of G and EG electrodes in 5mM potassium ferrocyanide electrolyte: In a 5mM potassium ferrocyanide solution containing 0.1MKCl, the electrochemical behavior of G electrode, EG-A electrode, EG-C electrode, and EG-AC electrode in potassium ferrocyanide was characterized using CV technology. Results are shown in Figure 5 , Figure 5 Figure A is the CV curve corresponding to the four electrodes obtained at a scan rate of 0.05 V / s. As can be seen from the figure, compared with the G electrode, the charging current of the EG-A electrode, EG-C electrode and EG-AC electrode after electrochemical stripping increases (the background current increases), indicating that the electroactive area of ​​the electrode has increased, which is conducive to increasing the adsorption sites. Compared with the G electrode, the redox peak current of the EG-A electrode, EG-C electrode and EG-AC electrode is also enhanced, and the current is 18.12μA, 63.64μA, 59.29μA, and 72.77μA, respectively, which indicates that the electrochemical performance of the original graphite foil is improved after partial stripping.

[0055] Electrochemical impedance spectroscopy (EIS) can characterize resistance characteristics and further compare the differences in conductivity between different electrodes. In the Nyquist plot, the smaller the diameter of the semicircle, the smaller the charge transfer resistance; the closer the straight line is to the vertical line, the smaller the electrode diffusion resistance, that is, the faster the ions diffuse inside the material, and the better the mass transfer capacity. Figure 5 Figure B shows the EIS measurement results of the G electrode, EG-A electrode, EG-C electrode, and EG-AC electrode. It can be found that the G electrode has the largest charge transfer resistance, which is related to the low conductivity of the original graphite foil. After the G electrode was partially stripped, the charge transfer resistance of the EG prepared by different stripping methods decreased to varying degrees. Among them, the semicircle diameter of the EG-C electrode is the smallest, which indicates that it has good electron transfer performance and high charge transfer efficiency. At the same time, the straight line of the EG-C electrode is also the most vertical compared to the EG-A electrode and the EG-AC electrode, that is, ion diffusion is easier. The semicircle diameter corresponding to the EG-A electrode is the largest because the continuous oxidation of the anodic stripping process causes the graphene produced to have obvious defects, and there are a large number of oxygen-containing groups between the graphite layers, which hinders the electron transfer process; the semicircle diameter corresponding to the EG-C electrode is the smallest because the cathode stripping produces low-defect, low-oxidation graphene.

[0056] The electrochemical behavior of CBZ on EG-AC reveals: Figure 6Figure A in the middle shows the corresponding cyclic voltammetry (CV) curves of the sensors of G electrode, EG-A electrode, EG-C electrode and EG-AC electrode in 0.2M PBS (pH 7.0) containing 50μM CBZ. It can be found that the redox peak current response of CBZ on the G electrode is weak and has a high oxidation potential, which indicates that the bare G electrode has low electron transfer kinetics and poor catalytic performance, and it is difficult to achieve high-sensitivity determination of CBZ. The CV curves of the sensors after electrochemical stripping show redox peaks of different sizes, among which the EG-AC electrode has a large oxidation peak at 0.762V, with a peak current of 85.6μA. When scanning in the negative direction, the reduction peak potential is 0.710V and the peak current is -51.5μA, indicating that the reaction of CBZ in the sensors of EG-A electrode, EG-C electrode and EG-AC electrode is an irreversible redox process. Compared with other electrodes, EG-AC shows a higher oxidation peak current response and a lower oxidation peak potential, indicating that the EG-AC electrode can be used for sensitive and low-potential CBZ detection.

[0057] The electrochemical performance of CBZ detected on G electrode, EG-A electrode, EG-C electrode and EG-AC electrode was compared by differential pulse voltammetry (DPV). Figure 6As can be seen from Figure B, in 0.2M PBS (pH 7.0) containing 50μM CBZ, the G electrode has a weak oxidation peak at 0.74V, and the oxidation peak current of CBZ is only 122.6μA. After the G electrode is partially stripped, the electrode's response current to CBZ is greatly improved. Among them, the peak current value corresponding to the EG-A electrode is 1045μA, and the signal intensity is increased by about 9 times. The reason is that after the graphite foil is stripped by the anode, it has more adsorption sites and oxygen-containing groups, which can interact with the analyte CBZ through hydrogen bonds, making it easier for the analyte to adsorb on the electrode surface, producing a unique catalytic effect and activity on the electrochemical behavior of CBZ, thereby enhancing the response current, but the background current of the EG-A electrode is extremely large, which is not conducive to trace detection. In comparison, the background current of the EG-C electrode is significantly reduced, and the peak current of CBZ increases to 1309μA, which is 25% higher than that of the EG-A electrode. The reason may be that the graphene formed by pure cathode stripping has fewer defects and good conductivity, so the peak current is significantly higher than that of the EG-A electrode; at the same time, due to the low degree of pure cathode stripping and low N and O heteroatom doping, the charging current caused is small, so the background current can be effectively reduced. The maximum response current of the EG-AC electrode is 1701μA, which is 30% higher than that of the EG-C electrode. This is mainly due to the embedding of an appropriate amount of oxygen-containing groups during anode stripping, which enhances the adsorption of the analyte. Considering the above CV and EIS results, it can be concluded that in order to improve the detection performance of CBZ, the electrode prepared by alternating anode and cathode stripping (EG-AC electrode) and the electrode prepared by cathode stripping alone (EG-C electrode) are more effective than the electrode prepared by anode stripping (EG-A electrode), and the EG-AC electrode has the best detection performance for CBZ.

[0058] Among them, during the alternating stripping of the anode and cathode, a large amount of low-defect graphene can be formed on the electrode surface when passing through the cathode potential, thereby increasing the electrode specific surface area and conductivity.

[0059] Figure 6 Figure C shows the DPV curves of the G electrode, EG-A electrode, EG-C electrode, and EG-AC electrode in PBS containing 1 μM CBZ. Figure 6 The trend presented in Figure B is similar.

[0060] The DPV technique was used to study the effect of pH on the electrochemical response of CBZ using the EG-AC electrode. Figure 7Figure A is the DPV curve of the EG-AC electrode in PBS solutions with different pH values ​​containing 1 μM CBZ after enrichment for 10 min at a potential of 0.35 V. It can be seen that pH has a significant effect on both the peak current and peak potential of CBZ. When the pH is 5-7, the oxidation peak current of CBZ increases with the increase of pH and reaches the maximum at pH = 7.0.

[0061] Example 3

[0062] This embodiment provides a use of a graphite foil electrode. The EG-AC electrode prepared in Example 1 is used in the detection of carbendazim (CBZ). The specific steps are as follows:

[0063] (1) Preparation of carbendazim standard solution: accurately weigh 0.00191 g of carbendazim standard into a 100 mL volumetric flask, add anhydrous ethanol and ultrasonically dissolve it, then dilute to obtain a 1 mM carbendazim standard solution, and store it at low temperature away from light to prevent deterioration of the carbendazim;

[0064] (2) Differential pulse voltammetry (DPV) was used to study the response current of CBZ on the EG-AC sensor prepared in Example 1 when the CBZ concentration was 0.001, 0.005, 0.025, 0.05, 0.1, 0.25, 0.5, 1, 1.5, 2, 2.5 and 3 μM. Figure 8 Figure B shows the linear curve of CBZ. In the range of CBZ concentration from 0.001 to 2 μM, I pa =0.3469c+22.267(R 2 =0.9942), and calculated that its minimum detection limit (LOD) could reach 0.24nM (S / N=3).

[0065] At pH 7.0, after 15 min of potential enrichment at 0.35 V, the response current of CBZ showed a significant enhancement trend with the increase of CBZ concentration, but the current increase trend slowed down after increasing to 2.5 μM. Figure 8 Figure A, the EG-AC sensor has good CBZ determination performance, with a low detection limit and a wide linear range.

[0066] Example 4

[0067] This embodiment provides a use of a graphite foil electrode. The EG-AC electrode prepared in Example 1 is used to detect actual samples containing carbendazim. Spiked recovery experiments of CBZ are performed in well water and pear juice, respectively. The specific steps are as follows:

[0068] Well water: Accurately pipette 1 mL of well water sample and dilute it with PBS solution. Then add CBZ standard solution to the well water sample using the standard addition method to prepare spiked samples with different CBZ concentrations.

[0069] Pear juice: Accurately weigh 10.00g of pear juice drink in a 50mL centrifuge tube, add a certain volume of CBZ standard solution to the pear juice drink (Master Kong rock sugar snow pear) according to the set concentration gradient, and prepare spiked samples with different CBZ concentrations. Accurately transfer 10mL of acetonitrile to the centrifuge tube containing the sample, vortex centrifuge for 2min, weigh 5g of anhydrous MgSO4 in the centrifuge tube, mix well and let stand for 20min to allow the solution to separate. Transfer to a centrifuge and centrifuge at 4000r / min for 10min, transfer 5mL of supernatant to a 15mL centrifuge tube containing 1g of anhydrous MgSO4 and 250mg PSA, and centrifuge at 4000r / min for 10min. After passing the supernatant through an organic filter membrane, it can be used for subsequent electrochemical determination.

[0070] Referring to Tables 1 and 2, three concentrations of low, medium and high were set, and the specified volume of CBZ was added to the well water and pear juice beverage samples in turn for spike recovery test. At an electrolyte pH of 7.0, 0.35 V potential was used for enrichment for 15 min, and then quantification was performed using the corresponding matrix standard curve.

[0071] The results are shown in Tables 1 and 2. The spiked recoveries of CBZ in the actual sample detection were between 79.3% and 91.9%, and the relative standard deviations (RSDs) were between 1.65% and 4.52%. The results show that the prepared EG-AC sensor can be used for the quantitative analysis of CBZ in actual samples.

[0072] Table 1

[0073]

[0074]

[0075] Table 2

[0076]

[0077] Example 5

[0078] This embodiment provides the use of graphite foil electrode EG-AC, with the following features:

[0079] Six EG-AC electrodes were prepared under the same conditions using the STEP technology. The reproducibility of the EG-AC sensor was verified using the DPV technology in a 0.2 M PBS solution containing 1 μM carbendazim. The measurement results showed a comparable peak current, and the calculated relative standard deviation (RSD) was 4.39%, confirming its good reproducibility.

[0080] In a 0.1 M PBS solution containing 1 μM CBZ, the DPV technique was used for 6 consecutive measurements, and the measurement results showed a comparable peak current, and the calculated relative standard deviation RSD was 4.05%, indicating that the sensor can be used repeatedly.

[0081] The anti-interference performance of the EG-AC sensor was evaluated by DPV test of 1 μM CBZ, and 50 times the concentration of K + 、Na + and Ca 2+ Common ions such as ions and organic substances such as glucose, fructose, and citric acid were used as interferences in the study. Fig. 9 As shown, the above 50 times of interfering ions have little effect on the detection of CBZ. Compared with the peak current signal of the solution without adding interfering ions, the changes in the oxidation peak current are all within 5%. The results show that the sensor has a strong anti-interference ability.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a graphite foil electrode, characterized in that: The following steps are involved: S1. Prepare a nitrate solution with a concentration of 0.5-2M as an intercalation reagent for standby use; S2, using intercalation reagent as electrolyte, graphite foil as working electrode, auxiliary electrode and reference electrode to form a three-electrode system; S3. Applying a step potential to the working electrode using a multi-potential step technique, and obtaining a nitrogen-oxygen doped partially exfoliated graphite foil electrode with the participation of nitrate ions, wherein the oxygen content of the graphite foil electrode is 15%-25%; the nitrogen content is 3%-10%; wherein the step potential is two cathode potential cycles, or one anode potential and one cathode potential cycle; When the step potential is a cycle of an anode potential and a cathode potential: the anode potential is 0.2V to 1.2V, and the cathode potential is -1.5V to -2.6V; the anode potential is maintained for 18-25s; the cathode potential is maintained for 8-15s; the cycle is 2-14 times; the absolute value of the difference between the anode potential and the cathode potential ranges from 2.7 to 3.1V.

2. The method for preparing a graphite foil electrode according to claim 1, characterized in that: In S3, the step potential is two cathode potential cycles: the first cathode potential is -0.2V to -0.6V, maintained for 18-25s; the second cathode potential is -1.7V to -2.1V, maintained for 8-15s; Repeat 2-12 times.

3. The method for preparing a graphite foil electrode according to claim 2, characterized in that: In S3, when the two cathode potentials are cycled: the first cathode potential is -0.6 V, maintained for 20 s; the second cathode potential is -2.1 V, maintained for 10 s; Repeat 2 times.

4. The method for preparing a graphite foil electrode according to claim 1, characterized in that: In S3, when the step potential is a cycle of an anode potential and a cathode potential: the anode potential is 0.6 V and maintained for 20 seconds; the cathode potential is -2.1 V and maintained for 10 seconds; Repeat 10 times.

5. The method for preparing a graphite foil electrode according to claim 1, characterized in that: In S1, The concentration of the nitrate solution is 1.5 M; The nitrate is selected from one of sodium nitrate, potassium nitrate and ammonium nitrate.

6. The method for preparing a graphite foil electrode according to claim 1, characterized in that: In S2, the working area of ​​graphite foil is 0.09-4cm 2 .

7. A graphite foil electrode for detecting carbendazim, characterized in that: Prepared by the preparation method described in any one of claims 1 to 6, comprising a graphite foil substrate and graphene nanosheets vertically distributed on the surface of the graphite foil substrate, wherein the graphene nanosheets and the graphite foil substrate are seamlessly connected; the graphene nanosheets and the graphite foil substrate are prepared by electrochemical exfoliation of a piece of graphite foil; The graphite foil electrode has an oxygen content of 15%-25% and a nitrogen content of 3%-10%.

8. An electrochemical sensor, characterized in that It comprises the graphite foil electrode according to claim 7 or the graphite foil electrode prepared by the preparation method according to any one of claims 1 to 6.

9. The electrochemical sensor according to claim 8, characterized in that The electrochemical sensor is a carbendazim detection sensor.

Citation Information

Patent Citations

  • Preparation method of graphite foil electrode and application of graphite foil electrode in electrochemical sensing

    CN112051314A

  • Preparation method and energy storage application of graphite foil electrode

    CN112117135A